Assessment of greenhouse gas emissions and mitigation opportunities of the Commercial Aviation Sector in Thailand - Arthit Champeecharoensuk; Dhakal, Shobhakar; Nuwong Chollacoop; Salam, P. Abdul; Kunnawee Kanitpong; RTG Fellow Scholarship; AIT Scholarships; NSTDA Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
The past ten years have seen significant growth in Thailand{u2019}s civil aviation sector, which has resulted in higher energy and greenhouse gas (GHG) emissions. The industry faces a substantial challenge in terms of GHG emissions as it is projected that the rapid growth in air transport will continue. Presently, the COVID-19 lockdown is loosened, and the country's opening up, domestic aviation and the economies of many countries are recovering quickly, causing fuel consumption and GHG emissions to rise once again progressively. The domestic aviation industry is uncontrolled in terms of GHG emissions, despite the ICAO{u2019}s CORSIA (International Civil Aviation Organization{u2019}s Carbon Offsetting and Reduction Scheme for International Aviation) rule being in effect for international aviation. This study has estimated and analyzed the pre-COVID-19 GHG emissions and their trends from commercial domestic aviation in Thailand. It provides insights into the role of key drivers that influence GHG emissions, and analyzes GHG emissions from this sector under various scenarios through 2050. It evaluates the influences of the mitigation policies, such as fuel switching, and aircraft technology, improving fuel efficiency due to technological advancements in aircraft and carbon pricing. Moreover, this study identifies the barriers to mitigation policies and measures, including a perspective on the possible ways to remove these barriers. Emissions are estimated following Intergovernmental Panel on Climate Change (IPCC) Tier-II. Specifically, activity-based landing/take-off (LTO) cycle and cruise. This is compared to the Tier-I method, and key drivers are analyzed using an index decomposition method. The results show that the total annual average GHG emissions for all LTO cycles and cruises of commercial domestic aviation for 2015-2020 was 2,254 Th. tonnes of CO2-eq. The choice of accounting methods (i.e., IPCC Tier II vs. Tier I) seems to have had only a nominal implication. Our analysis showed that, in the 2008-2020 period, the aviation activity effect and economic growth were the key decisive factors in this sector's GHG emissions growth. This was followed by the fuel energy intensity levels and the population effect in decreasing order of influence. Analysis of future scenarios shows that the fuel switching option would result in a significant long-term reduction in GHG emissions, whereas the carbon pricing option and aircraft technology option are more efficient for reducing GHG emissions in the short term. Simultaneously implementation of these measures can achieve higher mitigation target for short- and long-term mitigation effects; this comprehensive approach could lead to a 39% reduction in emissions compared to the reference future scenario. For identifying and ranking of barriers, this study involved 30 aviation experts and stakeholders, revealing a total of 20 key barriers categorized into Social, Technical, Financial, and Policy domains. Policy holds the highest relative weight, followed by financial, technical, and social factors. Policy serves as the driving force behind the development and support for the reduction of greenhouse gas emissions in the transportation sector of the country. Additionally, financial factors play a crucial role in facilitating the implementation of various policies in the future. This is because investments and technology development in Thailand require substantial financial support from the government and other relevant sectors to successfully attain the country's goals, which are further complemented by the country's technological advancements and societal aspects. These findings hold significant implications for both current and future GHG emissions reduction measures, supporting Thailand{u2019}s 2050 climate targets and energy efficiency policies if the domestic aviation industry adapts.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Sustainable Energy Transition
Thesis (Ph.D.) - Asian Institute of Technology, 2024
Keywords: Greenhouse gas mitigation -- Thailand; Aeronautics, Commercial -- Environmental aspects -- Thailand